2021
DOI: 10.21203/rs.3.rs-46985/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing configurations of Attractive Toxic Sugar Bait (ATSB) stations in Mali, West Africa, for improving the control of malaria parasite transmission by vector mosquitoes and minimizing their effect on non-target insects

Abstract: Background Attractive Toxic Sugar Baits (ATSBs) successfully reduced Anopheles mosquito vector populations and malaria parasite transmission in Mali, but application methods need to be improved for wide-scale use, and effects on non-target organisms (NTOs) must be assessed. The goals of this study were to determine on a village level the effect of different outdoor configurations of ATSB bait stations to 1) achieve > 25% Anopheles mosquito vector daily feeding rate for both males and females and 2) minimize… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Mosquitoes can probe and feed through pores in the membrane to access the sugar meal and the active ingredient. Environmental assessment and subsequent trials in Mali have demonstrated that when deployed within the ATSB, the toxicant poses limited risk to non-target organisms, including pollinators (11) and humans (ERM, 2021, unpublished ATSB Human Risk Assessment).…”
Section: Intervention: Atsbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mosquitoes can probe and feed through pores in the membrane to access the sugar meal and the active ingredient. Environmental assessment and subsequent trials in Mali have demonstrated that when deployed within the ATSB, the toxicant poses limited risk to non-target organisms, including pollinators (11) and humans (ERM, 2021, unpublished ATSB Human Risk Assessment).…”
Section: Intervention: Atsbsmentioning
confidence: 99%
“…Proof-of-concept studies in Mali also demonstrated the ability of ATSB to reduce malaria vector populations when the ingestion toxicant dinotefuran was included in bait stations (10). Studies in Mali have also established that two bait stations installed on opposite exterior walls of eligible structures at the height of 1.8 meters, were associated with at least 30% of target mosquitoes feeding on bait stations (11). Studies conducted in Mali in 2017 showed ATSBs reduced mosquito density, the proportion of older females, the proportion of sporozoite infected females, and the entomological inoculation rate (EIR).…”
mentioning
confidence: 97%
“…Proof-of-concept studies in Mali also demonstrated the ability of ATSB to reduce malaria vector populations when the ingestion toxicant dinotefuran was included in bait stations [10]. Studies in Mali have also established that two bait stations installed on opposite exterior walls of eligible structures at the height of 1.8 m were associated with at least 30% of target mosquitoes feeding on bait stations [11]. Studies conducted in Mali in 2017 showed ATSBs reduced mosquito density, the proportion of older females, the proportion of sporozoite-infected females, and the entomological inoculation rate (EIR).…”
Section: Introductionmentioning
confidence: 97%
“…These trials aim to assess the impact of the Westham ASTB ® on malaria morbidity when provided in addition to universal coverage with IRS and/or LLINs. Based on results from modeling studies it is hypothesized, based on previous studies in Mali [11], that deployment of ATSBs will result in a 30% or greater decrease in the malaria case incidence and parasite prevalence compared to universal vector control coverage alone (standard of care). Additional outcomes include the durability of ATSBs, entomological outcomes, community perceptions of ATSB, and human safety.…”
Section: Introductionmentioning
confidence: 99%
“…Attractive toxic sugar baits containing insecticides or compounds anti‐pathogens have been proposed for the control of sand flies and other dipterans in laboratory assays and the field in the last decades 22,23,49–56 …”
Section: Introductionmentioning
confidence: 99%